'Test n Treat' (TnT): a cluster randomized feasibility trial of on-site rapid Chlamydia trachomatis tests and treatment in ethnically diverse, sexually active teenagers attending technical colleges. (July 2019) - Oakeshott, P.; Kerry-Barnard, S.; Fleming, C.; Phillips, R.; Drennan, V.M.; Adams, E.J.; Majewska, W.; Harding-Esch, E.M.; Cousins, E.C.; Planche, T.; Green, A.; Bartholomew, R.I.; et al.
Abstract: Objectives: We conducted a cluster-randomized feasibility trial of 90-minute Chlamydia trachomatis tests and same day on-site treatment ('Test n Treat/TnT') in six technical colleges in London, England, to assess TnT uptake rates; follow-up rates; prevalence of C. trachomatis at baseline and 7 months; time to treatment; acceptability of TnT. Methods: Participants completed questionnaires and provided genitourinary samples at baseline and 7 months. Participants were informed that baseline samples would not be tested for 7 months and were advised to get screened independently. Colleges were randomly allocated 1:1 to intervention (TnT) or control (no TnT). One month and 4 months post recruitment, participants at intervention colleges were texted invitations for on-site free C. trachomatis tests. A purposive sample of students who did/did not attend for screening were interviewed (n = 26). Results: Five hundred and nine sexually active students were recruited: median age 17.9 years, 47% male, 50% black ethnicity, 55% reporting two or more sexual partners in the previous year. TnT uptake was 13% (33/259; 95% CI 8.9–17.4%) at 1 month and 10% (26/259; 6.7–14.4%) at 4 months with overall C. trachomatis positivity 5.1% (3/59; 1.1–14.2%). Follow-up at 7 months was 62% (317/509) for questionnaires and 52% (264/509) for samples. C. trachomatis prevalence was 6.2% (31/503) at baseline and 6.1% (16/264) at 7 months. Median time from test to treatment was 15 h. Interviews suggested low test uptake was associated with not feeling at risk, perceptions of stigma, and little knowledge of sexually transmitted infections (STIs). Conclusions: Despite high C. trachomatis rates at baseline and follow-up, uptake of testing was low. Like many countries, England urgently needs better sex education, including making STI testing routine/normal. Trial registration ISRCTN58038795